Implicações do habitus no cultivo das práticas de leitura: um estudo sobre os alunos ingressantes no Curso de Ciências Sociais da Universidade Federal do Norte do Tocantins – UFNT - COSTA, LARISSA RODRIGUES FARIAS DA (Universidade Federal do Tocantins, 2023)
The aim of this study was to investigate reading practices of students entering the Social Sciences course of the Federal University of Northern Tocantins - UFNT/Tocantinópolis, in